2014
DOI: 10.5812/thrita.19789
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Postoperative Complications of Coronary Artery Bypass Graft Surgery in the Elderly

Abstract: Background: Higher life expectancy and increased ischemic heart disease (IHD) have resulted in increasing number of the elderly patients undergoing cardiac surgeries. Age along with many other comorbidities influence the outcome of major surgeries in the elderly patients; hence, case selection before major surgeries is challenging. Objectives: The pure effect of age after adjusting for other major preoperative risk factors is on the center of debate in literature. Materials and Methods:In this retrospective st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Old age is a major significant risk factor of POCD ( 2 , 13 , 14 ). However, Hosseini et al reported that age alone is not a strong predictor of complications ( 15 ). Preoperative health status such as diabetes mellitus, hypertension, glomerular filtration rate, and left ventricular ejection fraction are also major contribution factors.…”
Section: Discussionmentioning
confidence: 99%
“…Old age is a major significant risk factor of POCD ( 2 , 13 , 14 ). However, Hosseini et al reported that age alone is not a strong predictor of complications ( 15 ). Preoperative health status such as diabetes mellitus, hypertension, glomerular filtration rate, and left ventricular ejection fraction are also major contribution factors.…”
Section: Discussionmentioning
confidence: 99%